The effect of melatonin supplementation on the plasma levels of 2-arachidonoylglycerol, ghrelin and hedonic eating intensity in overweight/obese females: A study protocol for a pilot randomized controlled trial - Malihe Karamizadeh; Azadeh Khalilitehrani; Neda Lotfi Yagin; Marzieh Akbarzadeh; Reza Mahdavi; Bahram Pourghassem Gargari (PLoS ONE, 2025)
Introduction Hedonic eating, reward-driven eating rather than out of biological needs, has been proposed as one of the important causes of overweight and obesity in recent years. Dopamine, endocannabinoids, opioids, and ghrelin are among the physiological factors associated with hedonic eating. Since the results of some previous animal studies have indicated the effectiveness of melatonin supplementation on the levels of endocannabinoids, and ghrelin, therefore this pilot study will investigate the effect of melatonin supplementation on plasma levels of endocannabinoid 2-arachidonylglycerol, ghrelin, and the intensity of hedonic eating in overweight/obese females. Methods In a randomized, double-blinded, placebo-controlled study, forty-six women with overweight/obesity and high hedonic eating intensity (total score of power of food scale > 2.5) will be recruited. They will receive either a 5 mg/day melatonin supplement (n = 23) or a placebo (n = 23) for 8 weeks. The primary outcomes, including the plasma levels of 2-arachidonylglycerol and ghrelin, and the intensity of hedonic eating will be assessed at the baseline and end of the study. Additionally, the secondary outcomes (dietary intake, and body weight) will be evaluated at the study’s onset, after four weeks, and upon completion of the intervention. A one-way analysis of covariance (ANCOVA) will be used to detect the effect of melatonin supplementation on outcome variables. Discussion Considering the positive effects of melatonin supplementation in reducing endocannabinoid levels, the expression of the ghrelin hormone gene, the level of ghrelin, and the cannabinoid receptor type 1 gene expression in animal studies, it is possible that in human subjects, it could impact the intensity of hedonic eating by lowering endocannabinoid and ghrelin levels. Trial registration The trial was registered with the Iranian Registry of Clinical Trials in June 2023 under the ID number IRCT20080904001197N22.